Variability of the Primary Productivity in the Yellow and Bohai Seas from 2003 to 2020 Based on the Estimate of Satellite Remote Sensing - Qingjun Fu; Xiao Yan; Qingchao Hong; Lei Lin; Yujie Zhang (Journal of Marine Science and Engineering, 2023)
Monitoring marine primary productivity (PP) is crucial for understanding changes in the marine ecosystem. Based on satellite data and the vertically generalized production model (VGPM), this study investigated the spatiotemporal distribution and long-term trend of PP in the Yellow and Bohai Seas (YBSs) from 2003 to 2020. By using the calibrated satellite data and optimized parameterization scheme, the accuracy of the PP results in the YBSs was significantly improved compared to online PP products. The annual mean PP in the YBSs from 2003 to 2020 was 523.8 mgC/(m2·d), with significant seasonal and interannual differences. Seasonally, PP in the Yellow Sea and the Bohai Sea exhibited bimodal (two peaks in May and October) and unimodal (one peak in June) variation, respectively. The magnitude of mean PP in the YBSs was ranked as spring > summer > autumn > winter, with spring PP (~1000 mgC/(m2·d)) contributing more than 40% of the annual PP. The annual mean PP in the YBSs showed an overall decrease from 2003 to 2020, with a decrease rate of 5–6 mgC/(m2·d)/y. The interannual variation of the PP was mainly related to the variability of the chlorophyll-a concentration and was essentially inverse to the phases of the Pacific Decadal Oscillation and the El Niño-Southern Oscillation.